Photo, thermal and chemical degradation of riboflavin - Sheraz, Muhammad Ali; Kazi, Sadia Hafeez; Ahmed, Sofia; Anwar, Zubair; Ahmad, Iqbal (Beilstein Journal of Organic Chemistry, 2014)
Riboflavin (RF), also known as vitamin B2, belongs to the class of water-soluble vitamins and is widely present in a variety of food products. It is sensitive to light and high temperature, and therefore, needs a consideration of these factors for its stability in food products and pharmaceutical preparations. A number of other factors have also been identified that affect the stability of RF. These factors include radiation source, its intensity and wavelength, pH, presence of oxygen, buffer concentration and ionic strength, solvent polarity and viscosity, and use of stabilizers and complexing agents. A detailed review of the literature in this field has been made and all those factors that affect the photo, thermal and chemical degradation of RF have been discussed. RF undergoes degradation through several mechanisms and an understanding of the mode of photo- and thermal degradation of RF may help in the stabilization of the vitamin. A general scheme for the photodegradation of RF is presented.
Keywords: chemical degradation; degradation products; photodegradation; riboflavin; stability; thermal degradation